2022
DOI: 10.5812/aapm-123723
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block for Children Undergoing Cardiac Surgeries via Sternotomy: A Randomized Controlled Trial

Abstract: Background: Ineffective management of postoperative pain following pediatric cardiac surgeries adversely affects a patient’s postoperative course. The erector spinae plane (ESP) block has been described in the literature regarding perioperative pain management. We hypothesized that bilateral ESP blocks in pediatric patients would decrease intraoperative fentanyl consumption, reduce the need for postoperative morphine consumption, and improve pain scores. Objectives: The aim of this double-blinded randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Finally, we included 16 studies which included 1110 patients for analysis (489 in ESPB and 621 in control), [ Figure 1 ]. [ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ] Table 1 summarizes the details of all the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we included 16 studies which included 1110 patients for analysis (489 in ESPB and 621 in control), [ Figure 1 ]. [ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ] Table 1 summarizes the details of all the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported 24-hr morphine consumption[ 14 15 16 17 18 19 20 21 ] and 5 studies[ 22 23 24 25 26 ] reported 48-hr opioid consumption. For 24-hr morphine consumption, there were 232 patients in ESPB group and 240 patients in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Two different randomized controlled trials investigated the impact of erector spinae plane (ESP) blocks in patients undergoing sternotomy. In the first, Gado et al 12 randomized 98 children aged 6 months to 7 years to pre-incision, bilateral, single-shot ESP blocks vs no block. 12 Intraoperative fentanyl and postoperative morphine consumption were significantly reduced in the block group.…”
Section: Enhanced Recovery After Pediatric Cardiac Surgerymentioning
confidence: 99%
“…In the first, Gado et al 12 randomized 98 children aged 6 months to 7 years to pre-incision, bilateral, single-shot ESP blocks vs no block. 12 Intraoperative fentanyl and postoperative morphine consumption were significantly reduced in the block group. The time to first postoperative opioid rescue medication was significantly delayed in the block group.…”
Section: Enhanced Recovery After Pediatric Cardiac Surgerymentioning
confidence: 99%
“…Conversely, Karacaer et al [ 49 ] noted no significant differences between the ESP block and control groups in terms of the pain score, sedation score, extubation time, and length of ICU stay. Gado [ 50 ] assessed the efficacy and safety of bilateral ESP blocks in pediatric patients undergoing cardiac surgeries through a median sternotomy. Perioperative opioid consumption was reduced in the ESP block group compared with the control group with comparable postoperative complications such as vomiting, itching, and respiratory depression.…”
Section: Fascial Plane Blocks For Cardiac Surgerymentioning
confidence: 99%